Policy, law and education for human rights in European Union: Legality and social needs dichotomy - Campina, Ana (2018)
Considering the Human Rights paradigm change in the present century, the international legality, as the education, needs and proceedings, it´s important to understand the reasons of this renew human, and consequently social, context, translated in the legality as in the way of living. The terrorist attacks and the extremely security international measures; the anti-Semitic ideology proliferation, the racism and discrimination dangerous rates; renew Refugees waves; the economic crisis conducting millions to the real poverty; social capacity absence to understand and (re)act according to the needs, facing the violence and Rights violations are the most important causes of the change analysis of this research. The European Union faces these problems and changings according the Human Rights protection law despite the different difficulties. However, all over the world, there is an important dichotomy between legality and social needs that should be a priority to the “powers” aiming the Human Rights promotion.